2018
DOI: 10.3390/healthcare6030078
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Case-Based Blended Learning Ecosystem to Optimize Precision Medicine: Reducing Overdiagnosis and Overtreatment

Abstract: Introduction: Precision medicine aims to focus on meeting patient requirements accurately, optimizing patient outcomes, and reducing under-/overdiagnosis and therapy. We aim to offer a fresh perspective on accuracy driven “age-old precision medicine” and illustrate how newer case-based blended learning ecosystems (CBBLE) can strengthen the bridge between age-old precision approaches with modern technology and omics-driven approaches. Methodology: We present a series of cases and examine the role of precision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…More in general, the implementation of the HIN approach falls within the more general process of refinement of the case-based educational research methods (CBL) coming with it [73][74][75][76], as the learner can: (i) browse a clinical case over time; (ii) train to detect the evolutions and the interactions of the health issues; (iii) represent a clinical case of multimorbidity synthetically, with a diagram; (iv) develop the ability of CRM. Finally, since the HIN model is based on Petri Nets, it is possible to support an automatic assessment of the learner's performance in the execution of the clinical exercises [77].…”
Section: Discussionmentioning
confidence: 99%
“…More in general, the implementation of the HIN approach falls within the more general process of refinement of the case-based educational research methods (CBL) coming with it [73][74][75][76], as the learner can: (i) browse a clinical case over time; (ii) train to detect the evolutions and the interactions of the health issues; (iii) represent a clinical case of multimorbidity synthetically, with a diagram; (iv) develop the ability of CRM. Finally, since the HIN model is based on Petri Nets, it is possible to support an automatic assessment of the learner's performance in the execution of the clinical exercises [77].…”
Section: Discussionmentioning
confidence: 99%
“…It is a practical tool to study the case-based description in both high-and low-resource settings concerning personalized medicine. This description further illustrates the patient's journey from "age-old precision thinking", in low-resource settings, progressing to "omics-driven" high-resource settings regarding precision medicine [104]. Another study by Ray and Goyal reported that increasing the use of rapid nucleic acid sequencing, along with proteomic-, epigenomic-and metabolomic-based tools to determine the molecular variability in host response, is promising for early diagnosis and personalized treatment in sepsis in India [100].…”
Section: Personalized Approach To Sepsis Managementmentioning
confidence: 94%
“…In a recent study, Podder et al demonstrated a potential solution to the current pandemic of overdiagnosis and overtreatment using a case-based blended learning ecosystem (CBBLE). In this learning ecosystem, a concerted team communication and collaborative learning between healthcare stakeholders provide evidence-based, patient-centred inputs across a web interface and this informational support increase the chances of accuracy and precision in terms of diagnosis and treatment facilitating the process of optimal patient-centred care 30…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…In our current patient, to gather evidence-based solutions in terms of treatment accuracy, VP, one of the authors of this case report, uploaded this patient’s deidentified care record onto an online accessible database to enable sharing of his clinical details and potential queries with global experts in the user-driven healthcare network through Tabula Rasa,30 the online social media platform of the CBBLE.…”
Section: Global Health Problem Analysismentioning
confidence: 99%